2017
DOI: 10.1038/nature22396
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 expression by tumour-associated macrophages inhibits phagocytosis and tumour immunity

Abstract: Programmed cell death protein 1 (PD-1) is an immune checkpoint receptor that is upregulated on activated T cells to induce immune tolerance.1,2 Tumor cells frequently overexpress the ligand for PD-1, programmed cell death ligand 1 (PD-L1), facilitating escape from the immune system.3,4 Monoclonal antibodies blocking PD-1/PD-L1 have shown remarkable clinical efficacy in patients with a variety of cancers, including melanoma, colorectal cancer, non-small cell lung cancer, and Hodgkin’s lymphoma.5–9 Although it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

45
1,397
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,637 publications
(1,558 citation statements)
references
References 32 publications
45
1,397
3
4
Order By: Relevance
“…Programmed cell death protein 1 (PD-1) is expressed by both lymphoid 2 and non-lymphoid immune cells, 3 , 4 and is up-regulated upon after engagement of T cell or B cell receptors on naïve lymphocytes. 2 , 4 Activation of PD-1 by its ligand PD-L1 induces down-regulation of lymphocyte proliferation and cytokine production, resulting in lymphocyte deletion.…”
Section: Introductionmentioning
confidence: 99%
“…Programmed cell death protein 1 (PD-1) is expressed by both lymphoid 2 and non-lymphoid immune cells, 3 , 4 and is up-regulated upon after engagement of T cell or B cell receptors on naïve lymphocytes. 2 , 4 Activation of PD-1 by its ligand PD-L1 induces down-regulation of lymphocyte proliferation and cytokine production, resulting in lymphocyte deletion.…”
Section: Introductionmentioning
confidence: 99%
“…Exchange of inhibitory Siglec-E with activating SigE16 (extracellular Siglec-E domain with transcellular activating human Siglec-16) showed T cell-dependent growth inhibition. In an adoptive transfer model, we demonstrated that Siglec-E on T cells is functionally involved, although the model we used, with OVA-specific OT-I T on myeloid cells and NK cells within the tumor (38,39). Further experiments are needed to understand the functional relevance of these immune-modulatory receptors, including Siglec-9 or PD-1, on cell types other than T cells.…”
Section: 0mentioning
confidence: 99%
“…Additionally, programmed cell death protein 1 (PD-1) and programmed cell death ligand 1 (PD-L1) may serve as a new regulatory 'checkpoint' for macrophages, given that macrophages express PD-1 in the tumour microenvironment (9). Because the C-C chemokine ligand 2 (CCL2) and colony-stimulating factor 1 (CSF-1) play critical roles in recruiting macrophages to neoplastic tissue, interest in therapeutics that target these Research. on May 12, 2018.…”
Section: Introductionmentioning
confidence: 99%